PERAN BAITUL MAL DALAM PENGELOLAAN TANAH YANG KEHILANGAN PEMILIK DAN AHLI WARIS PASCA TSUNAMI DI ACEH (Sebuah Kajian Yuridis) - EMK Alidar (State Islamic University North Sumatra, 2010)
Abstract: The Role of Treasury (bayt al-mâl) in Land Management of the Missing Owner and Heir in the Post-Tsunami Aceh. The land of the missing person or heir of ex-tsunami disaster occurred in Aceh in 2004 causes serious concern in administering eligible ownership and the right of management, which mounts to presumably very large scale spreaded throughout the province of Aceh. This essay is an attempt to discuss what kind of regulatory measures that have to be taken so that the legal status of the land could be determined and most importantly its use can be managed. The auhtor offers some principal concepts that will become alternative solution in this land management which include first, the property of the religion as found in Islamic jurisprudence, second, the property of state or community as found in Indonesian Civil Code, and third, Aceh customary law. The author argues that these three legal concepts run parallel with regulation that govern the land property, the owner or heir of which is no longer recognized, and thus it becomes under the communal ownership managed by the treasury. Thus, it can be asserted that the propety of the missing person or unknown heir is managed by the treasury as a quasi-authority for the interest of the community at large. As an acting agency, the treasury may be subject to legal precept stipulated in the above regulations.Kata Kunci: Aceh, bayt al-mâl, harta agama, imeum gampong